Frontiers in Climate Smart Food Systems: Outlining the Research Space - Whitfield, Stephen; Challinor, Andrew J.; Rees, Robert M (Frontiers Media, 2018)
Food systems, from the local to the global, face a complex set of challenges in the twenty-first century. As recognized in the latest round of the United National Framework Convention on Climate Change talks, it is clear that global targets for mitigating greenhouse gas emissions cannot be met without major alterations to agriculture and supply chains. At the same time, these systems must adapt to changing and uncertain climatic conditions. Across national and international agendas, agriculture plays a further central role in achieving food security, driving economic growth, alleviating poverty, and sustaining ecological functions and services. In reality, food and agriculture intersect with every one of the UN sustainable development goals (SDGs), underlining growing global concern for, sometimes highly contested debate over, sustainability in food systems.